Morbidity of gonococcal infection, pelvic inflammatory diseases and infertility in the Russian Federation and The Ural federal region - N. A. Gerasimova; N. P. Evstigneeva; N. P. Malishevskaya; N. V. Zilberberg; N. I. Skidan; N. V. Kungurov (Лечащий Врач)
The analysis of the population morbidity of gonococcal infection, PID, female and male infertility in the Russian Federation, the Ural Federal District and the Sverdlovsk region for the period 2008–2017 has been carried out. The results show incomplete registration of the incidence of gonococcal infection by indirect signs.